Evaluasi Kualitas Pelayanan Aplikasi Sambat Rene Ker pada Pemerintah Kota Malang dalam Meningkatkan Responsivitas Pengaduan Masyarakat Secara Online - Sutaji Sutaji; Fedianty Augustinah; Ika Devy Pramudiana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Responsive public service is an essential indicator of government governance quality. This study evaluates the quality of the Sambat Rene Ker application using the SERVQUAL theory (Parasuraman, Zeithaml, Berry, 1990) through five dimensions. Using a qualitative approach, data were obtained from interviews, observations, and community complaint documentation. The analysis indicates that the reliability dimension is fairly good but hindered by server stability issues (20% deficiency). The physical evidence dimension shows a simple interface, but access speed and professionalism require improvement (15%). Responsiveness is adequate for initial responses, but follow-ups are often slow and lack transparency (25%). Assurance demonstrates good security, but insufficient progress notifications reduce trust. In conclusion, this application positively supports public services in Malang but requires improvements in infrastructure, coordination, and outreach to enhance responsiveness. This research is relevant for evaluating policies and innovations in technology-based services.